Epithetische Versorgung von Nasenseptumperforationen: Ergebnisse mit individuell angepassten Obturatoren aus Silikon = Prosthetic treatment of nasal septal perforations : results with custom-made silicone buttons - Plath, Karim; Federspil, Philippe A. (HNO, 2016)
BackgroundPerforations of the nasal septum can be very disturbing for patients due to increased crust formation, nose bleeds, obstruction of nasal breathing and whistling sounds during nasal breathing. The aim of this study was to evaluate how the symptom burden can be alleviated by custom-made silicone buttons derived from an impression mold.Material and methodsA retrospective study was carried out to evaluate 45 patients with symptomatic septal perforations, who have been treated over a period of 8 years. The magnitude and localization of the perforations were measured on the impression molds as well as in situ in 28 patients. The symptoms were rated on a visual analogue scale (VAS) before and after treatment (response 64%).ResultsNo correlation was found between the size of the perforation and the distance from the nasal opening. Of the patients 31 (69%) still had the septal button in situ at the time of the last follow-up. The magnitude and localization of the perforation were not found to be predictors of treatment success. The following symptoms showed a highly significant improvement: crust formation (VAS median 75 vs. 31), nose bleeds (VAS median 50 vs. 0), obstruction of nasal breathing (VAS median 84 vs. 14) and whistling breathing sounds (VAS median 69 vs. 0). Unpleasant odor and symptoms of sinusitis did not show significant changes. The long-term septal button carriers rated the improvement with a median of 91% on the VAS.ConclusionThe success of prosthetic closing of septal perforations by a custom-made button still cannot be accurately predicted. The majority of patients were extraordinarily satisfied because the symptom burden could be significantly reduced.
Gesehen am 18.08.2017